2009
DOI: 10.3747/co.v16i1.261
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Reliability and Validity of the Edmonton Symptom Assessment System

Abstract: BackgroundSystematic symptom reporting by patients and the use of questionnaires such as the Edmonton Symptom Assessment System (ESAS) have potential to improve clinical encounters and patient satisfaction. We review findings from published studies of the ESAS to guide use of the system and to focus research. MethodsA systematic search for articles from 1991 through 2007 found thirty-nine peer-reviewed papers from 25 different institutions, thirty-three of which focused on patients with cancer. Observations, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(73 citation statements)
references
References 61 publications
1
69
0
Order By: Relevance
“…For example, the Edmonton Symptom Assessment Scale (ESAS), which was the most frequently utilized scale in the analyzed studies, has repeatedly been found to have only a modest or no association with the Hospital Anxiety and Depression Scale, and no valid cutoffs have been established for screening with the ESAS items on anxiety and depression. 25 The majority of studies did not include a specific psychological measure but did include general measures of quality of life or distress, which similarly fail to elucidate what aspects of life or distress improved as a result of the intervention. Mental health scales that have a robust evidence base for being able to validly and reliably assess psychological symptoms as well as changes in psychological symptoms were only used in 15 (25.4%) of the 59 studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Edmonton Symptom Assessment Scale (ESAS), which was the most frequently utilized scale in the analyzed studies, has repeatedly been found to have only a modest or no association with the Hospital Anxiety and Depression Scale, and no valid cutoffs have been established for screening with the ESAS items on anxiety and depression. 25 The majority of studies did not include a specific psychological measure but did include general measures of quality of life or distress, which similarly fail to elucidate what aspects of life or distress improved as a result of the intervention. Mental health scales that have a robust evidence base for being able to validly and reliably assess psychological symptoms as well as changes in psychological symptoms were only used in 15 (25.4%) of the 59 studies.…”
Section: Discussionmentioning
confidence: 99%
“…Retested patients must be in a stable condition with respect to the construct to be measured by the PRO. This situation is particularly problematic in PC settings because advanced cancer patients are prone to a faster rate of clinical deterioration [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ESAS seemed to "balance" physical and psychological domains, including DT, and to better capture the emotional symptom burden. Indeed, all ESAS versions have physical symptoms outnumber items which induced patients to perceive the focus to be more physical than psychological symptoms [23]. The KTRs' perception of emotional symptom burden is likely more important than any objective clinical parameters in determining the KTRs' quality of life because KTRs reported many stressors, namely fear of rejection, worries about the risk of infection and prior to clinic visits, repeated hospitalizations, socio-economic status, side effects of immunosuppressive therapy and changes in body appearance [54].…”
Section: Discussionmentioning
confidence: 99%
“…The urgency for standardized psychiatric and psychosocial screening for distress in KTRs is also supported by the high prevalence of alexithymia [20], defined as a difficulty in identifying and describing emotions. The most commonly used psychiatric screening tools are however time-consuming and difficult for patients to complete [21][22][23][24][25][26][27]. A pragmatic patient-centred symptom assessment tool with visual analogue scale, the Edmonton Symptom Assessment System (ESAS), has been validated in dialysis patients [28] and, recently, in a single kidney-transplant cohort [29][30][31].…”
Section: Introductionmentioning
confidence: 99%